2014
DOI: 10.3389/fncel.2014.00391
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ differentially modulates memory-related processes under basal and chronic stressor conditions

Abstract: Cytokines are inflammatory messengers that orchestrate the brain’s response to immunological challenges, as well as possibly even toxic and psychological insults. We previously reported that genetic ablation of the pro-inflammatory cytokine, interferon-gamma (IFN-γ), attenuated some of the corticosteroid, cytokine, and limbic dopaminergic variations induced by 6 weeks of exposure to an unpredictable psychologically relevant stressor. Presently, we sought to determine whether a lack of IFN-γ would likewise modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 123 publications
3
45
0
Order By: Relevance
“…Several recent studies have suggested that the IFN-γ acts as a negative regulator of hippocampal functions. For example, the IFN-γ-deficient mice have shown impaired spatial memory, increased neurogenesis, dendritic arborizations, and probability of pre-synaptic neurotransmitter release in the hippocampal sub-regions (Litteljohn et al, 2014;Monteiro et al, 2016). Furthermore, intracerebroventricular injection of IFN-γ impairs the induction of long-term potentiation (LTP), an electrophysiological correlate of learning and memory, in hippocampal slices of rats (Maher T et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have suggested that the IFN-γ acts as a negative regulator of hippocampal functions. For example, the IFN-γ-deficient mice have shown impaired spatial memory, increased neurogenesis, dendritic arborizations, and probability of pre-synaptic neurotransmitter release in the hippocampal sub-regions (Litteljohn et al, 2014;Monteiro et al, 2016). Furthermore, intracerebroventricular injection of IFN-γ impairs the induction of long-term potentiation (LTP), an electrophysiological correlate of learning and memory, in hippocampal slices of rats (Maher T et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…, the maintenance of LTP in the hippocampus is blocked by the IL-1 receptor antagonist, IL-1RA (53)). IFNγ, a molecule crucial for the immune response against viruses, is another inflammatory cytokine that can facilitate LTP and memory (54, 55). According to a recent report using IFNγ-deficient mice, endogenous IFNγ signaling can facilitate LTP by blocking GABA-mediated inhibition in the hippocampus (55).…”
Section: Facilitation Of Ltp By Cytokinesmentioning
confidence: 99%
“…Indeed, our data indicates that non-inherited forms of ID might result from alterations of the immune/MER41/cognition pathway. Such a dysfunction may be induced by the untimely or quantitatively inappropriate exposure of neurons to specific cytokines, notably IL-6 or IFN, which physiologically shape neurotransmission (Baier et al, 2009;Chourbaji et al, 2006;Gruol, 2015;Litteljohn et al, 2014;Victório et al, 2010) and are possibly involved in the immune/MER41/cognition pathway.…”
Section: Accordinglymentioning
confidence: 99%
“…Interferon gamma (IFN), the prototypical T Helper 1 (TH1) cytokine, is a T-cell derived proinflammatory molecule exerting several effects on innate immune cells and others on nonimmune cells including neurons (Litteljohn et al, 2014). Specifically, IFN was recently shown to be a social behavior regulator and to shape neuronal connectivity in rodents (Filiano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%